Raptor is critical for increasing the mitochondrial proteome and skeletal muscle force during hypertrophy. Issue 12 (12th November 2021) - Baraldo, Martina; Nogara, Leonardo; Dumitras, Georgia Ana; Tchampda Dondjang, Achille Homère; Geremia, Alessia; Scalabrin, Marco; Türk, Clara; Telkamp, Frederik; Zentilin, Lorena; Giacca, Mauro; Krüger, Marcus; Blaauw, Bert
Abstract: Loss of skeletal muscle mass and force is of critical importance in numerous pathologies, like age‐related sarcopenia or cancer. It has been shown that the Akt‐mTORC1 pathway is critical for stimulating adult muscle mass and function, however, it is unknown if mTORC1 is the only mediator downstream of Akt and which intracellular processes are required for functional muscle growth. Here, we show that loss of Raptor reduces muscle hypertrophy after Akt activation and completely prevents increases in muscle force. Interestingly, the residual hypertrophy after Raptor deletion can be completely prevented by administration of the mTORC1 inhibitor rapamycin. Using a quantitative proteomics approach we find that loss of Raptor affects the increases in mitochondrial proteins, while rapamycin mainly affects ribosomal proteins. Taken together, these results suggest that mTORC1 is the key mediator of Akt‐dependent muscle growth and its regulation of the mitochondrial proteome is critical for increasing muscle force.